Bioengineered silkworm model for expressing human neurotrophin-4 with potential biomedical application - Zhang, Wenchang; Li, Zhiqing; Lan, Weiqun; Guo, Hao; Chen, Feng; Wang, Feng; Shen, Guanwang; Xia, Qingyou; Zhao, Ping (Frontiers in Physiology, 2023)
Neurotrophin-4 (NT-4) is a neurotrophic factor that plays important roles in maintaining nerve cell survival, regulating neuronal differentiation and apoptosis, and promoting nerve injury repair. However, the source of sufficient NT-4 protein and efficient delivery of NT-4 remain a challenge. This study aims to express an activated human NT-4 protein in a large scale by genetically engineering silk gland bioreactor of silkworm as a host. We showed that the expression of human NT-4-functionalized silk material could promote proliferation of mouse HT22 cells when compared to the natural silk protein, and no obvious cytotoxicity was observed under the conditions of different silk materials. Importantly, this functional silk material was able to induce the potential differentiation of HT22 cells, promote peripheral neural cell migration and neurite outgrowth of chicken embryo dorsal root ganglion (DRG). All these results demonstrated a high bioactivity of human NT-4 protein produced in silk gland. Therefore, based on the silkworm model, the further fabrication of different silk materials-carrying active NT-4 protein with good mechanical properties and great biocompatibility will give promising applications in tissue engineering and neurons regeneration.